The Historical Development of Children's Rights and Its impact on Legitimate Politics and International Conventions - ELSHAARAWY, SANAA (Journal of Ecohumanism, 2024)
The research seeks to achieve a basic goal of shedding light on the historical development of the concept of children's rights and the extent of its impact on legitimate politics and international conventions, especially in light of what we are witnessing at the contemporary time of violations of children's rights and their repercussions on the respect of political systems for such rights through the activation of constitutional rules that provide for child protection, and the activation of mechanisms for the application of these texts, and this is what calls for addressing the concept of the legal personality of the child in ancient legislation such as the legislation of Hamo Rabi, and legislation Pharaonic, Greek and Roman, Then exposure to the position of Islamic law and international conventions on the rights of the child by answering the problem that the extent of the historical development of the concept of children's rights on legitimate policy and international conventions?